People’s perception on agricultural vulnerabilities to climate change and SLR in Bangladesh: adaptation strategies and explanatory variables (International Journal of Agricultural Research, Innovation and Technology, 2018)
The objective of this research is to evaluate people’s perception on vulnerabilities of agriculture and to explore effective adaptation options with identifying the underlying demographic, socio-economic and other relevant variables that influence the adaptation strategies in the sea level rise (SLR) hazard induced coastal areas of Bangladesh. The study finds that climate change and induced SLR are emerging threats to coastal agriculture of Bangladesh; hence, farmers are applying different adaptation strategies to reduce the vulnerabilities of coastal agriculture. Selection of effective adaptation strategies to vulnerabilities of agriculture depends not only on the magnitude, intensity and the impacts of climate change and SLR, but also perceptions and types of farmer, land, educational level, indigenous knowledge about adaptation, locational advantages, external support, community awareness and sharing of different effective mechanisms among the farmers. Effective adaptation strategies with high perceptions have significant influence to reduce the vulnerabilities of agriculture considering the adverse impacts of climate change and SLR. In time of extreme climatic hazards when a great loss in agriculture hamper the coastal agrobased economy, different effective indigenous local adaptation strategies through farmer awareness and community co-operation become vital for minimizing the impact of climatic hazards and reducing the vulnerabilities of coastal agriculture.Int. J. Agril. Res. Innov. & Tech. 8 (1): 70-78, June, 2018